AIP Conference Proceedings 2007
DOI: 10.1063/1.2820924
|View full text |Cite
|
Sign up to set email alerts
|

Student Understanding Of The Physics And Mathematics Of Process Variables In P-V Diagrams

Abstract: Students in an upper-level thermal physics course were asked to compare quantities related to the First Law of Thermodynamics along with similar mathematical questions devoid of all physical context. We report on a comparison of student responses to physics questions involving interpretation of ideal gas processes on P-V diagrams and to analogous mathematical qualitative questions about the signs of and comparisons between the magnitudes of various integrals. Student performance on individual questions combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 3 publications
2
49
0
5
Order By: Relevance
“…Some of their demonstrated difficulties seem to have origins in the understanding of the math concepts themselves. These results are consistent with results from questions about integrals in thermodynamics contexts [8]. This aspect of our results will be explored further in future research.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some of their demonstrated difficulties seem to have origins in the understanding of the math concepts themselves. These results are consistent with results from questions about integrals in thermodynamics contexts [8]. This aspect of our results will be explored further in future research.…”
Section: Discussionsupporting
confidence: 80%
“…We have asked physics-less physics questions about integrals and line integrals, based on findings in the context of P-V diagrams [7,8] and about partial differentiation and the product and chain rules based on findings related to material properties in thermodynamics [5,9]. Our findings suggested that these questions were challenging to a significant population of physics students at the upper division.…”
Section: Methodsmentioning
confidence: 80%
“…[44], pp. [4][5][6][7][8][9]. Students who ranked the probabilities as simply P A ð1Þ > P A ð2Þ > P A ð3Þ also made claims that are consistent with some of Smith's other classifications.…”
Section: Incorrect Reasoning About Probability Ratiosmentioning
confidence: 54%
“…The study of student understanding of advanced topics is becoming increasingly prevalent in physics education research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Investigating upper-division undergraduate students provides a snapshot of the intellectual journey from novice introductory student to expert physicist that may reveal key components of this transition [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a positive correlation between student difficulties with physics concepts and those with either the mathematics concepts, application of those concepts, or the representations used to connect the mathematics and the physics. Students lacking and/or failing to apply relevant mathematical knowledge and skills have shown difficulties with reasoning and/or solving problems in physics contexts [2,3,12,13].…”
Section: Introductionmentioning
confidence: 99%